NUCLEAR FLUORESCENCE EMPLOYING ANTINUCLEOSIDE IMMUNOGLOBULINS - Klein, William J. (The Rockefeller University Press, 1967)
Fluoresceinated antinucleoside globulins were shown to react with the nuclei of L cells. The pattern of nuclear fluorescence was similar to the distribution of nuclear DNA. This reaction was shown to be specific by the following control experiments: 1. Absorption of the specific antibody from an antiadenosine globulin eliminated all fluorescence. 2. Treatment of the cells with nonfluorescent antiadenosine globulin, followed by staining with the fluorescent antiadenosine eliminated almost all of the fluorescence of the nucleus. 3. Treatment of the cells with DNase destroyed the ability of the nucleus to react with antiuridine fluorescent antibodies. 4. Fluoresceinated anti-BSA did not produce nuclear fluorescence. Nuclear fluorescence occurred only in cells harvested during the period of maximum DNA synthesis as measured by the uptake of thymidine. This correlates with the previously demonstrated specificity of the antibodies for denatured DNA.